The relationship of serum vaspin level with clinical parameters in patients with fibromyalgia syndrome - Elbastı, Muhammet Şahin; Kaçar, Emine (Cellular and Molecular Biology Association, 2024)
Vaspin plays a regulatory role in lipid and glucose metabolism and is a therapeutic adipokine against impaired glucose intolerance in obese individuals. We aimed to investigate serum vaspin levels in patients with FMS and whether there was any relationship between vaspin levels and metabolic and clinical parameters in fibromyalgia. A total of 64 female patients who applied to an outpatient clinic due to widespread pain lasting more than three months were included in the study. The patients were divided into two groups: 32 in the fibromyalgia group and 32 in the healthy controls. The socio-demographic characteristics of the patients were evaluated with the standard evaluation form. Age, weight, height, blood pressure, body mass index (BMI), waist circumference, presence of menopause were recorded. Pain intensity was evaluated with visual analogue scale (VAS). The Fibromyalgia Impact Scale (FIS) was utilized to measure quality of life and functional status. Metabolic syndrome components were significantly different in the fibromyalgia group compared to the control group (p <0.05). While 22 patients (68.8%) in the fibromyalgia group met the diagnostic criteria for metabolic syndrome, three patients (9.4%) in the control group met these criteria. In the fibromyalgia intra-group correlation, vaspin was significantly positively correlated with BMI and waist circumference (p<0.05). In the control group, vaspin indicated a statistically significant positive correlation with BMI. This study elaborated that waist circumference, insulin, and insulin resistance were significantly higher in the fibromyalgia patients compared to the healthy control group. This was confirmed by the finding that significantly more patients met the diagnostic criteria for metabolic syndrome. Additionally, vaspin was considerably higher in fibromyalgia patients and thus it was positively correlated with BMI and waist circumference. © 2024 Cellular and Molecular Biology Association. All rights reserved.
Keywords: FMS (fibromyalgia syndrome); Metabolic Syndrome; Obesity; Vaspin; Waist Circumference